Legal aid in crisis : assessing the impact of reform / Sarah Moore and Alex Newbury. - Moore, Sarah E. H., 1979-; Newbury, Alex (Policy Press shorts. Policy & practice., 2017)
This book is the first to evaluate the recent reforms of UK legal aid from a social policy perspective and assess their impact on family law courts and advocacy. It argues that the reforms effectively 'delawyerise' disputes, producing a more inquisitorial justice system and impacting the litigants, court system, staff and process.